Community Service Activity Through Health Education on Knowledge Improvement and Prevention of HIVAIDS: Community Health Education on HIV/AIDS - Suwardha Yunus; Irawati Anwar; Iwan (CV. Paperhome Indonesia, 2026)
HIV/AIDS is an Acquired Immunodeficiency Syndrome(AIDS) disease, namely a collection of symptoms of the disease caused by the Human Immunodeficiency virus (HIV) found in human body fluids. This disease is a global health threat because cases continue to increase, so it requires substantially innovative health services with effective prevention such as educational counseling, and counseling by health workers, it is very important to pay attention to how the disease is transmitted. This disease counseling provides general information on preventing HIV AIDS with the hope that sufferers will continue to live socially well, improve their quality of life and prevent new cases and improve continuous treatment services for sufferers. Counseling with lecture, discussion and question and answer methods by both sufferers and the general public, prevents unpleasant stigma and discrimination in society against HIV AIDS sufferers, the results of this activity found that 80% of respondents knew about HIV/AIDS and 20% of respondents did not know, therefore this counseling provides information to the public that what should be avoided is the disease, not the sufferer.